Phytopathology in Plants 2016
DOI: 10.1201/b13127-7
|View full text |Cite
|
Sign up to set email alerts
|

- Strategies of Nitrosomonas europaea 19718 to Counter Low Dissolved Oxygen and High Nitrite Concentrations

Abstract: Background: Stripe rust of wheat, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most important diseases of wheat worldwide. Due to special features of hexaploid wheat with large and complex genome and difficulties for transformation, and of Pst without sexual reproduction and hard to culture on media, the use of most genetic and molecular techniques in studying genes involved in the wheat-Pst interactions has been largely limited. The objective of this study was to identify transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…We speculated these transcripts represent new candidate genes for rust resistance in switchgrass. Transcripts of unknown function have also been reported in wheat yellow rust and leaf rust resistance studies (Wang et al, 2010; Raman et al, 2011). Out of the identified homologs, 29 are expressed proteins with no known function.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…We speculated these transcripts represent new candidate genes for rust resistance in switchgrass. Transcripts of unknown function have also been reported in wheat yellow rust and leaf rust resistance studies (Wang et al, 2010; Raman et al, 2011). Out of the identified homologs, 29 are expressed proteins with no known function.…”
Section: Resultsmentioning
confidence: 91%
“…This was similar to what was reported for leaf rust resistance in wheat ( Triticum aestivum L.), where differential expression between the resistant and susceptible cultivars was found after 48 hpi, with the highest abundance appearing at 96 hpi (Raman et al, 2011). The profusion of the stress‐tolerance‐related transcripts may be attributed to recognition of the pathogen by the host resistance genes before 60 hpi and initiation of the defense mechanism in host cells carrying the resistance gene against the rust pathogen (Bolton, 2009; Wang et al, 2010). We speculate that the expression of genes by the moderately resistant progenies is caused by massive reprogramming of the moderately resistant plant cells to restrict pathogen invasion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the expression of TaNH2 was found to be induced by Pst infection. As a previous study shown (Wang et al ., ), the up‐regulation of host genes during infection may indicate the exploitation of cellular resources and/or the activation of defense responses, suggesting that TaNH2 is involved in wheat resistance. In addition, TaNH2 was shown to positively regulate wheat resistance characterized by decreased necrotic area, reduced ROS accumulation and increased uredia production in TaNH2 ‐knockdown plants (Figure and Figure S15).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were described by Wang et al . () where 94 wheat genes were preferentially induced during the compatible interaction compared to the incompatible interaction of stripe rust between 12 to 24 h post‐infection. In addition, rice variety Nipponbare, carrying the resistance gene Pia , showed differential gene expression when infected with the rice blast ( Magnaporthe oryzae ) isolate P91‐15B (compatible interaction) compared to when infected with isolate Ina 86‐137 (incompatible interaction; Kawahara et al ., ).…”
Section: Introductionmentioning
confidence: 99%